Progressive 3D mesh generation - Nghiem, Viet Nam (2010)
One important aspect for any 3D graphics application is 3D shape representation. In every graphics application, there always exists a trade-off between complexity and performance. The more realistic 3D representation comes at a price of high computational complexity. In recent years, a new type of 3D shape representation, i.e. progressive mesh, has been received much attention since it provides a nice balance between complexity and performance. In this thesis, we focus on generating progressive meshes in two scenarios: from a given complex 3D textured model, and from a set of calibrated and segmented multi-view images.